PETRONAS Scholars I - Center - Nor Hafizah binti Idris, Nor Hafizah (Universiti Teknologi PETRONAS, 2012)
Aligning to the objective of the project, this report is produced for the purpose of designing the documentation of the project‟s development. At the end of this project course, a prototype of PETRONAS Scholars I – Center shall be the main goal to be achieved. For PETRONAS Scholarship program, current media used by PETRONAS Scholars and Sponsorship & Talent Sourcing (STS) unit in Universiti Teknologi PETRONAS (UTP) is not effective in several aspects such as difficulty faced by scholars in suiting time with STS staff to have a meeting for issues‟ clarification, lack of transparency or written documents defining processes and procedures related to scholarship program and no specific established medium used for communication among both parties. Reflected to that, this project is designed for PETRONAS Scholars and STS unit as an effective initiative to enhance communication and sharing medium among those parties that covers elements of scholarship‟s announcements and news, financial and claim information especially describing on process and procedures involve, STS contact details as well as feedback and discussion purposes. Using Rapid Application Development (RAD) as development methodology, the research conducted involves interview, survey and document analysis. Other than system testing conducted by developer, it requires user usability testing to measure users‟ acceptance towards the project. Results from this, it is concluded that the PETRONAS Scholars I - Center satisfies users‟ requirements and ready to be implemented.